MAKNA SENI LUKIS HITAM PUTIH KARYA I.G.N NURATA TAHUN 1990-2010 - Maraja Sitompul (Pascasarjana Institut Seni Indonesia Surakarta, 2013)
This article is the result of a study entitled â€œA Study of the Meaning of Black and White Paintings by I.G.N. Nurata from1990-2010.â€ The study takes as its object the black and white paintings of I.G.N. Nurata as a medium of expression, andaims to: 1) describe and analyze the background to the creation of I.G.N. Nurataâ€™s black and white paintings; 2) describe andanalyze the form of I.G.N. Nurataâ€™s black and white paintings; and 3) describe the response of the observer towards I.G.N.Nurataâ€™s black and white paintings. In order to obtain the necessary results, the research method adopted a holistic approachwhich focussed on six of I.G.N. Nurataâ€™s black and white paintings. The method used for collecting data included abibliographical study, participatory observation, documentation, and interviews. The data was analyzed mainly through aninterpretational analysis. Based on the results of the research, it could be concluded that: 1) I.G.N. Nurataâ€™s black and whitepaintings between 1990 and 2000 are visualized strongly in imaginary forms, through traditional visual language andcultural codes, in order to articulate symbolism and metaphors; 2) I.G.N. Nurataâ€™s black and white paintings between 2001and 2010 are still visualized in imaginary form, through traditional visual language and cultural codes, with the addition ofan increasingly intense use of elements of modern visual language such as the use of volume and perspective; and 3) On thewhole, there is a message of harmony between the macro, micro, and meta cosmos, in accordance with the doctrine â€œTri HitaKaranaâ€ which teaches us how to live in harmony with God, with other people, and with nature, including the spiritualworld.Keywords: Symbols through imaginative form, Visual Metaphors, Black and White Paintings